Speculating the Symbio: Possibilities for Multispecies and Multi-Entity World Making in Childhood - O'Brien, Shelley (Journal of Childhood Studies, 2022)
In this paper, I attempt to interrupt conventional analyses of childhood and instead illustrate the importance of diverse stories around child-nature relations. Vital materialist perspectives dismantle and disrupt binaries, so by exploring these perspectives, I am decentering the (adult) human and thinking-with the possibilities for multispecies relations in precarious times. This paper finishes with a speculative story that proposes lively experiments in multispecies and multi-entity possibilities, in a near-future contaminated Toronto. Enabled by microbes that have flourished on a shipwreck of e-waste, children, birds, and a dog codiscover the Symbio.